2008
DOI: 10.1002/cncr.23248
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic determinants of regional lymph node metastasis in early colorectal cancer

Abstract: BACKGROUND. Early colorectal cancer (ECC) is curable by endoscopic local resection; however, 10% of patients with ECC exhibit lymph node (LN) metastasis. In the current study, accurate predictors for LN metastasis in patients with ECC were examined by using immunohistochemistry with the lymphatic endothelial hyaluronan receptor 1 (LYVE‐1) antibody to discriminate between lymphatics and blood vessels. METHODS. Colorectal tissue specimens obtained from 71 patients with ECC, including 28 patients with regional LN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 35 publications
1
72
0
1
Order By: Relevance
“…Previous studies using different scoring systems such as those proposed by Hase, Nakamura, Ueno and Wang [7][8][9][10][11][12][13][14][15][16][17] have demonstrated that tumor budding is a strong independent prognostic parameter; however, the implementation of these results in clinical practice is hampered by the lack of a standardized scoring system. In a previous study by our group, after comparison of the several existing scoring methods, the 1 HPF and 10 HPFs approaches came out as the most reliable and reproducible methods of assessing tumor budding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using different scoring systems such as those proposed by Hase, Nakamura, Ueno and Wang [7][8][9][10][11][12][13][14][15][16][17] have demonstrated that tumor budding is a strong independent prognostic parameter; however, the implementation of these results in clinical practice is hampered by the lack of a standardized scoring system. In a previous study by our group, after comparison of the several existing scoring methods, the 1 HPF and 10 HPFs approaches came out as the most reliable and reproducible methods of assessing tumor budding.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] Moreover, tumor budding has repeatedly been linked to unfavorable disease outcome and has been shown to have an independent adverse effect on disease-free and overall survival. [1][2][3][4][5][6][7][8][9][10][11][12][13] Although tumor budding has been recognized by the International Union for Cancer Control as an additional prognostic factor in colorectal cancer, it remains largely unreported in daily diagnostic work. In contrast to other cancers, including breast and prostate cancer where scores are used in daily routine, there has not been real progress with respect to additional prognostic factors or scoring systems in colorectal cancer.…”
mentioning
confidence: 99%
“…16,19,22,25,26,29,30,37,43,44 In the largest of these studies, Ueno et al 26 demonstrated that, in submucosally invasive colorectal carcinoma, high tumor grade, lymphovascular invasion, and tumor budding are the three factors independently associated with lymph node metastases. Patients without any of these three features showed exceptionally low rates of lymph node metastases (1%, 1/138); in the presence of one risk factor, the rate of nodal metastases increased substantially to 21% (12/58), and when two or three factors were present, the risk was 36% (20/55), suggesting that in the absence of these factors, polypectomy alone is sufficient treatment for early colorectal carcinoma provided the resection margins are clear.…”
Section: Tumor Budding In Early Colorectal Carcinomamentioning
confidence: 99%
“…12,13,22,23,31,32,38,40,43,44,48,51,54,55 The use of immunohistochemistry in the assessment of budding is somewhat controversial: some authors argue that the evaluation of budding should be limited to H&E-stained slides because of the cost and impracticality of performing immunohistochemistry in routine cases, while others argue that immunohistochemistry should be used routinely to improve the accuracy and reproducibility of bud counts. In addition to cost considerations, the use of immunohistochemistry may also require the establishment of a separate cutoff for defining positive budding.…”
Section: Role Of Immunohistochemistry In the Evaluation Of Buddingmentioning
confidence: 99%
“…A significant association between tumor budding and lymph node positivity has been consistently demonstrated correlating with tumor aggressiveness and more advanced TNM stage [32][33][34][35][36][37][38][39][40][41][42][43] . Tumor budding is frequently associated with poorly differentiated tumors, and with the presence of vascular and lymphatic invasion independently of disease extent [44][45][46][47][48] .…”
Section: Prognostic Impact Of Tumor Buddingmentioning
confidence: 99%